2009
DOI: 10.1111/j.1365-2702.2008.02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbal product use in a sample of Turkish patients undergoing haemodialysis

Abstract: Aim.  To examine herbal product use among patients with end‐stage renal disease undergoing haemodialysis. Background.  Herbal therapy is a very popular choice for many patients. However, little information is available about herbal product use in renal patients. Design.  The study was designed as a cross‐sectional survey. The data were obtained from 114 end‐stage renal disease patients in two haemodialysis centres in Ankara, Turkey between June–August 2007. Methods.  Data were collected through face‐to‐face st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 37 publications
7
34
1
4
Order By: Relevance
“…11 Similarly, poor communication between patients and health care professionals regarding herbal product use was also reported by other studies. 14,19,20 Respondents using herbal medicines without informing the treating physician may have to bear the brunt of serious clinical implications due to the possible herb-drug interactions. It has been found that herbal products interact or interfere with the normal pharmacology of some drugs with potentially fatal consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Similarly, poor communication between patients and health care professionals regarding herbal product use was also reported by other studies. 14,19,20 Respondents using herbal medicines without informing the treating physician may have to bear the brunt of serious clinical implications due to the possible herb-drug interactions. It has been found that herbal products interact or interfere with the normal pharmacology of some drugs with potentially fatal consequences.…”
Section: Discussionmentioning
confidence: 99%
“…13 Similarly, Kara, and Rivera et al reported from studies in the Turkey and USA respectively that people generally follow the trusted advice of family members and friends. 14,15 Reliance on the family advice about herbal use indicates a general lack of scientific attitude among users. Herbal remedies are as old as humankind but their traditional use is not a good indicator of its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…KBY hastalarında TAT yöntemlerinin kullanımının incelendiği çalışmalarda bu tedavileri daha çok kadınların 11,12,13 , 51-70 yaş arasındaki hastaların 11 , eğitim düzeyi yüksek olanların 11,15,16 , evlilerin 17 ve çalışanların 16 tercih ettiği bildirilmiştir.…”
Section: Kronik Böbrek Yetmezliği Hastalarının Kullandığı Tamamlayıcıunclassified
“…KBY hastalarının bitkisel destekleri %16.8 ile %45 arasında değişen oranlarda kullandığı bildirilmiştir 2,11,14,17,20 . En çok tercih edilen bitkisel destekler ise sarımsak 11,15,17,19 , ıhlamur çayı 11,19 , ada çayı 11 , bitki çayları 13 , ısırgan 15,19,20 , maydanoz 15,19 , kutsal mantar (holy mushroom), spiderworth (telgraf çiçeği), boesenbergia (böğürtlen) 2 (38). Özdemir ve ark.…”
Section: Doğal üRünler (Bitkisel üRünler)unclassified
See 1 more Smart Citation